Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) dengan Media Roda Putar terhadap Hasil Belajar Mahasiswa Program Studi Pendidikan Biologi STKIP Pembangunan Indonesia - Azis, Putri Athirah; Pertiwi, Nova Dwi (Universitas Negeri Makassar, 2019)
Abstract. This study aims to determine the effect of the use of the TGT cooperative learning model with rotary wheel media on the learning outcomes of STKIP Pembangunan Indonesia students. This type of research is a quasi-experimental which takes two classes, the experimental class and the control class. The subjects of this study were even semester 2018/2019 students. The study was conducted in each class as many as 8 hours of study. The technique of data collection in this study uses instruments in the form of test results in the form of multiple choices. Data analysis using descriptive statistics using percentages and inferential statistics with t-test. The results showed that (a) from the results of the descriptive analysis, the mean value of the learning outcomes of the experimental class biology students 77.20 while in the control class 65.05 (b) from the results of inferential analysis using the confidence level t0.05 found that. The critical area H0 is rejected if p value (Sig. (2-tailed)) = 0.027. Because the test statistic is p value (Sig. (2-tailed)) <0.05 then H0 is rejected so it can be concluded that there is an effect of learning outcomes between students taught using the TGT cooperative learning model with rotary wheel media and without using the TGT cooperative learning model with rotary wheel media. Keywords: cooperative learning model type TGT, media wheel rotate, learning outcomes.